2016
DOI: 10.3390/nu8090563
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Properties of Herba Epimedii and Its Main Bioactive Componentsicariin and Icariside II

Abstract: Cancer is one of the leading causes of deaths worldwide. Compounds derived from traditional Chinese medicines have been an important source of anticancer drugs and adjuvant agents to potentiate the efficacy of chemotherapeutic drugs and improve the side effects of chemotherapy. Herba Epimedii is one of most popular herbs used in China traditionally for the treatment of multiple diseases, including osteoporosis, sexual dysfunction, hypertension and common inflammatory diseases. Studies show Herba Epimedii also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 87 publications
0
45
0
Order By: Relevance
“…12 A number of studies have explored the ability of ICA II to modulate the invasivity and migratory capabilities of lung, gastric, and esophageal cancer cells. 10,16 Herein, we determined that ICA II was able to signi cantly inhibit DU145 PC cell invasion and migration.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…12 A number of studies have explored the ability of ICA II to modulate the invasivity and migratory capabilities of lung, gastric, and esophageal cancer cells. 10,16 Herein, we determined that ICA II was able to signi cantly inhibit DU145 PC cell invasion and migration.…”
Section: Discussionmentioning
confidence: 98%
“…13,14 Several different anti-tumor drugs seek to modulate these activities via either disrupting tumor cell proliferation and/or via inducing apoptotic tumor cell death. 10,15 Traditional herbal medicines represent a potentially ideal source of compounds for use in chemotherapeutic regimens, 16 with drugs such as camptothecin, paclitaxel, and emodin all having been developed from natural plant sources. 17,18 Previous work has demonstrated that ICA II is capable of mediating anti-tumor activity against hepatic carcinoma, breast cancer, and gastric cancer via a range of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epimrdii Herba (Epimedium) [8] is a TCM originating from Epimedium Brevicornu Maxim., Epimedium sagittatum Maxim., Epimedium pubescens Maxim., or Epimedium koreanum Nakai. It has been reported to treat diseases [9] such as cancer, osteoporosis, cardiovascular disease and brain disease, it also improves sexual function. Coicis Semen is a mature dry kernel of the gramineous plant Coix lacryma-jobi L. var.…”
Section: Introductionmentioning
confidence: 99%